Wake up Muffin - Paragon (Paragon Book, 1999)
This book contains a beautiful collection of simple stories, perfect for reading at bed time or any time of the day. turn the page and let a cast of wonderful characters fill your dreams with fun and magic.
Keywords: Stories for young reader